Kamusi ya diplomasia na uhusiano wa kimataifa. - Baraza la Kiswahili la Taifa (Tanzania) (Dar es Salaam : Baraza la Kiswahili la Taifa, 2013)
A Swahili-English dictionary of diplomatic and foreign relations terms.
In Swahili and English.
Keywords: Diplomacy -- Dictionaries -- Swahili; International relations -- Dictionaries -- Swahili; English language -- Dictionaries -- Swahili